Mitochondria in innate immunity - Arnoult, Damien (Nature Publishing Group, 2011)
Mitochondria are cellular organelles involved in host-cell metabolic processes and the control of programmed cell death. A direct link between mitochondria and innate immune signalling was first highlighted with the identification of MAVS—a crucial adaptor for RIGI-like receptor signalling—as a mitochondria-anchored protein. Recently, other innate immune molecules, such as NLRX1, TRAF6, NLRP3 and IRGM have been functionally associated with mitochondria. Furthermore, mitochondrial alarmins—such as mitochondrial DNA and formyl peptides—can be released by damaged mitochondria and trigger inflammation. Therefore, mitochondria emerge as a fundamental hub for innate immune signalling.